Prática docente: uma investigação sobre o ensino de língua espanhola em uma cidade do Sul de Minas Gerais - Santos, Patrícia Keli dos (2019)
The present study is a case study, a descriptive, exploratory and qualitative study, whose general objective is to investigate the teaching work of four teachers of Spanish Language in two public schools and two private schools in a city in the South of Minas Gerais. As specific objectives the research focuses on: i) presenting the context of teaching Spanish Language in public and private schools; ii) describe how the Spanish Language has been worked in the classroom in both contexts iii) compare the didacticpedagogical practices of teachers and the use of digital technology in the public school with those of the private school teachers. Our concern has arisen from the moment that teaching a foreign language, especially the Spanish language, is challenging, since it is necessary to deal not only with the difficulties of practice itself, but also with the current context of "devaluing" the teaching of this language. subject. The proposal of analysis was based on theoretical studies based on Correa (2009), Almeida Filho (2009) Martínez-Cachero Laseca (2009), Rajagopalan (2011), Moita Lopes (2006), Gatti (2008), among others. Therefore, it was sought to focus only basic questions for the contextualization of the theme chosen for the research. In this way, to relate the pedagogical practice and the teaching of the Spanish Language made it possible to raise some questions about the pedagogics of the teachers of Spanish Language in the classroom. For the purpose of analyzing the teaching practice, this research had a period of two months of observation of classes, and, therefore, a data survey was also carried out through field notes and questionnaires. For the analysis of the data of the investigation we use the PDT for the codification of the data and creation of the categories of analysis. The results highlight that the Spanish language, even with the lack of resources, is being effectively worked out in the public and private schools analyzed. The teachers investigated intend to train themselves and are worried about working with pedagogical practices that improve the quality of their classes, seeking to use digital technologies. It is hoped that this research will serve as a theoretical contribution for future research on the teaching of Spanish Language.